Vince Flynn : order to kill : a Mitch Rapp novel - Flynn, Vince, 1966-2013; Mills, Kyle, 1966- (Flynn, Vince, 1966-2013. Mitch Rapp novel, 2016)
Rapp heads to Pakistan to confront a mortal threat he may not be prepared for. In fact, this time he might have met his match. Mitch Rapp is used to winning. But now the CIA operative finds himself chasing false leads from continent to continent in an effort to keep nukes from falling into the hands of terrorists. Together with friend and colleague Scott Coleman, Rapp struggles to prevent the loss of these lethal weapons, and soon it becomes alarmingly clear that forces in Moscow are hell-bent on fomenting even more chaos and turmoil in the Middle East. Rapp must go deep into Russian territory, posing as an American ISIS recruit, to stop a plan much more dangerous and insidious than he ever expected.